AvR-CHOP: Feasibility Study of Induction and Maintenance Avelumab Plus R-CHOP in Patients with Diffuse Large B-Cell Lymphoma (DLBCL) - Hawkes, Eliza A; Manos, Kate; Smith, Charmaine; Hawking, Joanne; O'Brien, Stephanie; Churilov, Leonid; McKendrick, Joseph; Renwick, William; Grigg, Andrew; Witkowski, Tom; Scott, Andrew; Lee, Sze-Ting; et al. (Blood, 2019)
Background: Whilst up to 60% of DLBCL patients (pts) are cured with frontline R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone), outcomes remain poor for those with relapsed or refractory disease. 1 New strategies to improve frontline cure rates are needed. Tumour cells exploit immune checkpoint pathways, including the PD1/PDL1 axis, to evade the host immune system. PD1/PDL1 over-expression and cytogenetic 9p24 alterations in some DLBCL subtypes provide additional rationale for immune checkpoint inhibition (ICI) in this disease. Although single agent PD1 inhibition yields an overall response rate (ORR) of only 10%-30% in heavily pre-treated unselected DLBCL, many responses are durable.2 Immunosuppressive effects of prior therapy may contribute to the modest response to ICI in relapsed disease. A number of considerations influence the incorporation of ICI into upfront DLBCL treatment. Although concurrent PD1/PDL1 inhibition and R-CHOP is safe,3 corticosteroid-related immunosuppression may negate PDL1-inhibitor efficacy. Evidence supporting host immune priming with ICI prior to chemotherapy is promising,4 and maintenance ICI post chemotherapy may assist with immune reconstitution and enhance the anti-tumour immune response. Additionally, avelumab (Av, an anti-PDL1 monoclonal antibody with antibody dependent cellular cytotoxicity activity) acts synergistically with rituximab (R) in vitro (unpublished data, Pfizer 2016). Thus, we present our phase II study assessing the safety of sequential Av+R induction, R-CHOP and Av maintenance as upfront therapy for DLBCL. Methods: AvR-CHOP (NCT03244176) is a phase II multicentre single-arm trial of Av induction + maintenance with R-CHOP in newly-diagnosed adult pts with DLBCL. Pts aged >18 years, ECOG 0-2, stage II-IV and with no active autoimmune disease are eligible. Exclusion criteria include the necessity for urgent cytoreduction, grade 3B or transformed follicular lymphoma, CNS involvement, chronic steroid use, prior transplantation or pneumonitis. Treatment (Fig 1) comprises R (375mg/m2 IV) + Av (10mg/kg IV) x 2 cycles q2-weekly, followed by R-CHOP21 x 6 cycles. Maintenance Av x 6 cycles q2-weekly is given to patients achieving a complete metabolic response by PET/CT at the end of R-CHOP. PET/CT is performed after R+Av 2 cycles, cycle 2 R-CHOP, end of R-CHOP and end of Av maintenance. The primary endpoint is immune-related toxicity within 30 days post-treatment. Secondary endpoints include ORR, failure free survival (FFS), overall survival (OS) and toxicity of treatment. Complete metabolic response rates by PET-CT after R-Av induction and after C2 R-CHOP are exploratory endpoints. Biomarker sample collection is synchronised with PET response assessment. A comprehensive translational substudy will apply high throughput technologies to tissue and sequential blood samples to characterise the tumour-immune system interaction and correlate novel host, tumour and tumour microenvironment factors with treatment responses and toxicity. Planned enrolment is 28 pts across 3 sites in Australia. The study follows a Simon 1 stage design, with an 80% power and a 1-sided alpha of 0.05 to rule out an Av-related toxicity rate of 30% (p0=70%), assuming an expected immune related toxicity rate of 10% [p1=90%]. 23 pts are enrolled to date. Acknowledgements: Merck KgA (avelumab and funding) References: 1. Cunningham D et al. Rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisolone in patients with newly diagnosed diffuse large B-cell non-Hodgkin lymphoma: a phase 3 comparison of dose intensification with 14-day versus 21-day cycles. Lancet (London, England). 2013;381(9880):1817-26. 2. Ansell SM et al. Nivolumab for Relapsed/Refractory Diffuse Large B-Cell Lymphoma in Patients Ineligible for or Having Failed Autologous Transplantation: A Single-Arm, Phase II Study. J Clin Oncol. 2019;37(6):481-9. 3. Nowakowski GS et al. Safety and efficacy of PD-L1 inhibitor durvalumab with R-CHOP or R2-CHOP in subjects with previously untreated, high-risk DLBCL. Journal of Clinical Oncology. 2019;37(15_suppl):7520-. 4. Park SE et al. Increased Response Rates to Salvage Chemotherapy Administered after PD-1/PD-L1 Inhibitors in Patients with Non-Small Cell Lung Cancer. Journal of thoracic oncology : official publication of the International Association for the Study of Lung Cancer. 2018;13(1):106-11. [Display omitted] Hawkes:Roche/Genentech: Membership on an entity's Board of Directors or advisory committees, Other: Travel expenses, Speakers Bureau; Bristol-Myers Squibb: Research Funding, Speakers Bureau; Astra Zeneca: Research Funding; Celgene: Membership on an entity's Board of Directors or advisory committees, Research Funding; Merck KgA: Research Funding; Janssen-Cilag: Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Mundi pharma: Research Funding; Gilead: Membership on an entity's Board of Directors or advisory committees, Research Funding; Roche: Research Funding; Takeda: Speakers Bureau; Merck Sharp & Dohme: Membership on an entity's Board of Directors or advisory committees. Manos:NovoNordisk Pharmaceuticals: Other: Travel; Janssen: Honoraria. Renwick:Celgene: Consultancy; Roche: Honoraria. Grigg:MSD: Membership on an entity's Board of Directors or advisory committees; Abbvie: Membership on an entity's Board of Directors or advisory committees; Janssen: Membership on an entity's Board of Directors or advisory committees; Roche: Other: Travel. Scott:Medimmune: Consultancy; Abbvie: Consultancy, Patents & Royalties; IBA: Consultancy; Avipep: Consultancy; Life Science Pharmaceuticals: Equity Ownership; Paracrine Therapeutics: Equity Ownership, Patents & Royalties; NHMRC: Research Funding; Cancer Australia: Research Funding; Cancer Council Victoria: Research Funding; Cure Brain Cancer: Research Funding; Humanigen: Patents & Royalties. Lee:Australian Nuclear Science and Technology Organisation: Membership on an entity's Board of Directors or advisory committees. Fong:Astellas: Consultancy; Amgen: Consultancy, Research Funding, Speakers Bureau; Pfizer: Consultancy, Speakers Bureau; Novartis: Speakers Bureau. Rooney:GenesisCare: Employment. Wight:Janssen: Honoraria; Takeda: Honoraria; Abbvie: Honoraria; BMS: Other: Travel; Amgen: Other: Travel. Chong:BMS: Research Funding; Merck Serono: Research Funding; Bayer: Research Funding; Novartis: Research Funding; Hutchison Medipharma: Research Funding; Pharmacyclics: Research Funding. Avelumab is an anti-PDL1 monoclonal antibody.